Educação Ambiental e o Ensino de Ciências no livro de pano - Charqueiro, Dina Mara Mildred (2019)
The objective of this research is to investigate if the cloth book used in the teaching and learning process of Science Teaching and Environmental Education during the dynamics of the three pedagogical moments (3MP), can promote the construction of scientific knowledge about the Pantanal. The predominant methodological approach in this study is qualitative, exploratory and descriptive. The research was developed in a municipal school of Campo Grande - MS, with 17 students of the 2nd year of Elementary School, with ages between 7 and 8 years. The activities of this research were developed in 06 hours / class, based on the three pedagogical moments proposed by Delizoicov and Angotti (1990), consisting of Initial Problematization (PI), Knowledge Organization (OC), and Knowledge Application (AC). To analyze the data obtained in the production of mind maps by the participants, we used the Kozel Methodology (2007), which proposes to analyze the signs that are reflected in the social and cultural construction on the individual's worldview. The contents in Science Teaching can be used as an important strategy for the promotion of Environmental Education in the classroom, by working with the environmental aspects allows the awareness about the environmental problems. The results reinforce the idea that it is necessary to work on scientific literacy using different teaching materials that can facilitate the teaching and learning of students who are in the process of literacy. Therefore, it is necessary to question the teaching of science and environmental education in the early years of basic education.